Pengaruh Model Cooperative Learning Tipe Student Facilitator And Explaining Terhadap Motivasi Belajar IPS Siswa Kelas V SD N 08 Woja - Julkifli (SEHRAN (Jurnal Pendidikan Sejarah dan Kewarganegaraan), 2023)
This research is to determine the effect Cooperative Learning Model Student Facilitator and Explaining Types of Social Science Learning Motivation for Students. This research was conducted at SD N 08 Woja using only one class, namely class V. This research method is a pre-experimental design method with the type of One Group Pre-test and Post-test design. Data collection in this study was in the form of a questionnaire or questionnaire and documentation. Based on the data analysis that has been done it can be concluded that the use of the Cooperative Learning model of the Student Facilitator and Explaining type can influence student learning motivation in class V SD N 08 Woja. Whereas based on the calculation of the t-test that has been carried out on the pretest value and posttest value, it is obtained that tcount obtains a value of 11.96 and ttable is 1.670 so that the result is tcount > ttable which means H1 is accepted and H0 is rejected. So, it can be concluded that there is an influence of social science learning motivation using the Cooperative Learning model of the Student Facilitator and Explaining Type.